Iron distribution of the Moon observed by the Kaguya gamma-ray spectrometer: Geological implications for the South Pole-Aitken basin, the Orientale basin, and the Tycho crater - Naito, M.; Hasebe, N.; Nagaoka, H.; Shibamura, E.; Ohtake, M.; Kim, K.J.; Wöhler, C.; Berezhnoy, A.A. (Icarus (New York, N.Y. 1962), 2018)
In this study we describe the distribution of iron on the Moon as obtained by the Kaguya high energy resolution gamma-ray spectrometer (KGRS). We achieved for the first time the identification of iron based on the fast neutron flux obtained by the KGRS. The iron distribution obtained by KGRS is compared to that of the Lunar Prospector Gamma-Ray Spectrometer (LP GRS), showing that the FeO distributions observed by KGRS and LP GRS, in general, are in good agreement. Furthermore, we compare the iron content data obtained by KGRS and LP GRS to spectral reflectance measurements of the Clementine, Kaguya and Chandrayaan-1 spacecraft as well as those inferred from returned samples. We found differences in FeO concentration and distribution in areas of moderate abundance (6–15 wt%) of the South Pole-Aitken basin, Mare Orientale, and around the crater Tycho crater. It implies that high concentrations of FeO at Mare Ingenii in the South Pole-Aitken basin and Mare Orientale are due to the presence of mare basalts, whereas the enriched FeO content in the central depression of the South Pole-Aitken basin and the Tycho crater indicates the presence of mafic materials such as impact melt breccia.